(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4028.44-54 The article presents reflections (theoretical and empirical) on the interfaces between the solidarity economies in Brazil and public policies. In this sense, it is a reflection on the interrelations between state, economy and society. The approaches are: 1. How to institutionalize solidarity economy (SE) in the structures of the state? What are the interrelationships between the SE and other public policies? How to establish permanent and effective instruments of participation of SE in management policies? The solidarity economy contemporary experiences would be inducing new models of public action? Or in other words, the experiences would be manipulated by the mechanisms of power and money as Jurgen Habermas argues in his theory of communicative action? There are no simple answers, experiences in solidarity economy is configured as a constant building process.